The Need for Specialized Pediatric Cardiac Critical Care Training Program in Limited Resource Settings - Murni, Indah K.; Musa, Ndidiamaka L. (Frontiers in Pediatrics, 2018)
Congenital heart disease (CHD) is one of the major global health problems with the highest birth prevalence in low- and middle-income countries. In these populous countries, basic health services for the children with CHD, including surgery, are lacking. Even though surgery is performed, outcome after cardiac surgery is influenced by the quality of the postoperative management with a reported high morbidity and mortality. Henceforth, there is an urgent need for comprehensive interventions to provide high quality cardiac intensive care programs to improve the quality of pediatric cardiac surgery services in order to address high morbidity and mortality after cardiac surgery. The development and training of the health workers in the field of pediatric cardiac intensive care program is required. It is imperative to conduct this training prior to actual implementation of the program in limited resources settings.